2016
DOI: 10.1186/s13223-016-0170-9
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus march: from ABPA to aspergilloma to subacute invasive aspergillosis

Abstract: Background Aspergillus is a ubiquitous fungus responsible for allergic as well as saprophytic and invasive manifestations depending on host’s immune status. The following case report demonstrates progression of allergic manifestations of Aspergillus to its invasive form in an individual with decreasing immunity. This can lead to uncertainties in diagnosis and management.Case presentationA 28-year-old male, non smoker, known case of ABPA (allergic bronchopulmonary aspergillosis) was admitted with complaints of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In our case, adjunctive surgery resulted in ABPA remission for 2 years. Previous studies have reported the outcome of surgical resection for aspergilloma in ABPA patients, due to pneumothorax [ 8 ] and hemoptysis [ 9 , 10 ]. However, only one case involved a report of surgical resection for aspergilloma that contributed to disease control of ABPA; the patient was followed up without ABPA treatment for 6 months after receiving surgical resection for aspergilloma with antifungal therapy [ 11 ], whereas our case was followed up for a number of years.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, adjunctive surgery resulted in ABPA remission for 2 years. Previous studies have reported the outcome of surgical resection for aspergilloma in ABPA patients, due to pneumothorax [ 8 ] and hemoptysis [ 9 , 10 ]. However, only one case involved a report of surgical resection for aspergilloma that contributed to disease control of ABPA; the patient was followed up without ABPA treatment for 6 months after receiving surgical resection for aspergilloma with antifungal therapy [ 11 ], whereas our case was followed up for a number of years.…”
Section: Discussionmentioning
confidence: 99%
“…Acute IA occurs rapidly with clinical presentation ranging from days to 3–4 weeks. Sub-acute invasive aspergillosis (SAIA) typically occurs in patients who are not profoundly immunocompromised but may be very debilitated and usually runs a slowly progressive course over 4–12 weeks [ 25 ]. IA may be angio-invasive and non-angio-invasive with angio-invasion being especially common in neutropenic patients with invasive pulmonary aspergillosis (IPA).…”
Section: Invasive Aspergillosismentioning
confidence: 99%
“…pulmonary aspergillosis (aspergilloma or fungus ball) is the best-recognized form of pulmonary involvement due to Aspergillus, usually occurring in a preformed cavity in the lung (due to tuberculosis, sarcoidosis, or other necrotizing pulmonary processes) or in the paranasal sinuses [8,9]. Subacute invasive aspergillosis (also called chronic necrotizing pulmonary aspergillosis) is a locally destructive invasion of lung parenchyma without invasion or dissemination to other organs [9,10].…”
Section: Aspergillosismentioning
confidence: 99%